Does the Wage System Play a Role in Maintaining Employee Loyalty? - Hariyanti, Sri; Kristanti, Desi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Every employee who works definitely needs appropriate compensation or remuneration from the company. Compensation is one of the reasons why employees work. The purpose of this research is to determine the wage system and employee loyalty at UD. Al Amien and to find out the role of the wage system on employee loyalty in that place. The location of this research is on Jl. Ahmad Yani No. 200, Gabru, Banyuanyar, Kec. Gurah, Kediri Regency. This research uses a descriptive qualitative approach, namely a method used to examine objects in natural conditions. The researcher acts as a key instrument in the data collection process which is carried out by observation, interviews, and recording or documentation and the research results emphasize meaning rather than generality. The results of this research show that the wage system implemented by UD. Al Amien is very flexible and is given every week according to the number of employee attendance. Employee loyalty is also quite high, this is reflected in good performance and compliance with applicable regulations. Even though the company provides wages below the minimum wage standards set by the government, employees still feel satisfied and consider these wages to be sufficient for their daily needs.